Targeting Parenting in Early Childhood: A Public Health Approach to Improve Outcomes for Children Living in Poverty - Morris, Amanda Sheffield (Child Dev, 2017)
In this article, the authors posit that programs promoting nurturing parent–child relationships influence outcomes of parents and young children living in poverty through two primary mechanisms: (a) strengthening parents’ social support and (b) increasing positive parent–child interactions. The authors discuss evidence for these mechanisms as catalysts for change and provide examples from selected parenting programs that support the influence of nurturing relationships on child and parenting outcomes. The article focuses on prevention programs targeted at children and families living in poverty and closes with a discussion of the potential for widespread implementation and scalability for public health impact.